Hydrogen production by oxidative reforming of ethanol in a fluidized bed reactor using a PtNi/CeO2SiO2 catalyst. (17th May 2019) - Ruocco, Concetta; Palma, Vincenzo; Ricca, Antonio
Abstract: Oxidative steam reforming of ethanol (OESR) was investigated over PtNi/CeO2 SiO2 catalysts prepared from different cerium salt precursors. During stability tests performed at 500 °C, steam/ethanol ratio (S/E) of 4 and oxygen/ethanol ratio of 0.5 (O/E), the highest performance was recorded over the catalyst prepared form organic precursors. The most promising formulation was tested at different temperatures, S/E and O/E. Complete conversion was recorded during 100 h of the test at 600 °C, with a very low carbon formation rate (6.9·10 −7 gcoke, oxidized ·gcatalyst −1 ·gcarbon, fed −1 ·h −1 ). The increase of oxygen content in the reacting mixture from 5 to 7.5% had a beneficial effect on H2 yield, which rose of more than 20% after 100 h of test, and on the conversion of by-products. When steam/ethanol ratio grew from 4 to 6, a slightly lower performance improvement was observed. Therefore, the highest activity and stability during OESR over the PtNi/CeO2 SiO2 catalyst prepared from organic salts was achieved at 600 °C, O/E = 0.75 and S/E = 6. Graphical abstract: Image 1 Highlights: Organic precursors improved the stability of PtNi catalysts for ethanol reforming. A temperature rise of 100 °C was more effective than a H2 O/C2 H5 OH ratio growth to 6. Improved H2 yield were observed by increasing oxygen content from 5 to 7.5%. When the steam content grew to 60%, C2 H4 O disappeared in the products stream.